Kajian Pustaka : Pemanfaatan Mikroba Yang Berpotensi Sebagai Agen Bioremediasi Limbah Pewarna Tekstil [A Review : Utilization of Potential Microbes as Bioremediation Agent for Textile Dyes Waste water] - Valerie, Valerie; Pinontoan, Reinhard (Universitas Pelita Harapan, 2018)
The rapid expansion of textile industry in Indonesia raises substantial concerns with regard to the disposal of excess dyes into the environment. The deleterious consequences of such issue can be alleviated through wastewater management by combining physical, chemical and biological approach. Biological treatment through bioremediation needs to be thoroughly considered and developed as it offers favorable attributes by being sustainable, inexpensive and environmentally friendly. In Indonesia, the employment of bioremediation technique, to treat textile dye effluent, has been extensively applied through the use of activated sludge. Apparently, studies describing the potential of various indigenous microorganisms to degrade textile dyes have continuously been reported. This paper proposed practical methods to isolate and select for potential indigenous microbes as well as their employment as bioremediation agent on dye contamination. Selections can be enhanced through the incorporation of bioinformatics analysis on the approach of microbiology. Appropriate systems are required to be carefully designed to optimized application on-site.